웹 2.0 방식의 직무역량모델링 방법 개발 - 황은동(Eun-Dong Hwang); 정윤민(Yun-Min Jung); 김수연(Soo-Yeon Kim) (한국콘텐츠학회 논문지, 9(2), 2009)
Many companies in Korea have developed job competency models and are utilizing them for the purpose of training and management of employees. However many of them are unable to be utilized efficiently through their own job competency model because the company failed to reflect what happens in the real work place in the model or the model itself is not concrete enough to be applied practically. Thus, in this study, the current status of Korean companies which had developed their own job competency model were investigated and the subsequent development of training system which is based on the model were developed. By result of the survey, about 43.5% of the company, which has more than 400 employees, have developed job competency models and 31.7% of them haven‘t been able to develop training system based upon the model due to the lack of concreteness of their model. To overcome this contradiction, we developed web 2.0 based job competency modeling method where each individuals in the organization themselves develop job competency as opposed to an expert oriented developing method. The result of this study is that web 2.0 based job competency modeling method is superior to any another modeling in an accuracy of competency, an acceptance of competency, and an usefulness of competency description. 현재 상당수 기업에서 인력육성 및 관리 분야에 활용하는 직무역량모델은 현장 업무를 반영하지 못하거나 개발된 직무역량 모델이 실제 활용에 구체적이지 못해 업무 활용도가 떨어지는 상황이다. 한국 기업의 직무역량모델 개발 현황과 이를 기반으로 한 교육체계 개발 현황을 조사한 결과, 종업원 400인 이상 기업의 43.5% 정도가 직무역량모델을 개발했으며, 직무역량모델을 개발한 기업 중 31.7%는 만들어진 역량이 상세하지 못해 직무역량을 기반으로한 교육체계를 개발하지 못하고 있는 것으로 조사되었다. 본 연구는 문제 해결을 위해 '웹 2.0방식의 직무역량모델링 방법'을 소개하고 이러한 방법으로 개발한 직무역량모델과 대부분 기업의 직무역량을 개발하는 방식인 전문가 중심의 개발된 직무역량모델을 비교 분석하였다. 연구 결과는 웹 2.0 방식의 개발한 직무역량모델에 대해 역량명의 정확성, 수용성 그리고 역량기술서의 유용성이 뛰어난 것으로 나타났으며, 기업의 환경에 맞는 구체적인 역량이 도출된 것으로 조사되었다.